Incidence of Acute Myeloid Leukemia and Myelodysplastic Syndrome in Patients With Inflammatory Bowel Disease and the Impact of Thiopurines on Their Risk. (26th April 2021) - Khan, Nabeel; Patel, Dhruvan; Trivedi, Chinmay; Kavani, Himanshu; Pernes, Tyler; Medvedeva, Elina; Lewis, James; Xie, Dawei; Yang, Yu-Xiao
Abstract : INTRODUCTION: Acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS) are rare myeloid clonal disorders that commonly affect the elderly population and have poor prognosis. There are limited data on the risk of AML/MDS among patients with inflammatory bowel disease (IBD), especially on the impact of thiopurines (TPs). METHODS: We conducted a retrospective cohort study among patients with IBD from Veteran Affairs data set. The exposure of interest was TP exposure: (i) never exposed to TPs, (ii) past TP use (discontinued >6 months ago), (iii) current TP use with a cumulative exposure of <2 years, and (iv) current TP use with a cumulative exposure of ≥2 years. The outcome of interest was a composite outcome of incident diagnosis of AML and/or MDS. Cox regression was used to estimate the adjusted and unadjusted hazard ratios (HRs) with 95% confidence intervals (CIs) for AML/MDS risk associated with TP use defined as a time-varying exposure. RESULTS: Among 56, 314 study patients, 107 developed AML/MDS. The overall incidence of AML/MDS in the IBD population was 18.7 per 100, 000 patient-years. The incidences among those never exposed to TPs, past users of TPs, current users of TPs with a cumulative exposure of <2 years, and current users of TPs with a cumulative exposure of ≥2 years were 17.0, 17.7, 30.4, and 30.3 per 100, 000 patient-years, respectively. In multivariable Cox regression analysis, compared with never exposed to TPs, current use of TPs was associated with increased risk (adjusted HR 3.05; 95% CI 1.54–6.06, P = 0.0014 for current use of TPs with a cumulative exposure of <2 years and adjusted HR 2.32; 95% CI 1.22–4.41, P = 0.0101 for current use of TPs with a cumulative exposure of ≥2 years), whereas past TP exposure was not. DISCUSSION: Among patients with IBD, current TP use was associated with an increased risk of AML/MDS, which reverts to baseline after discontinuation of TP use.